Usefulness of the CAT, LCOPD, EQ-5D and COPDSS Scales in Understanding the Impact of Lung Disease in Patients with Alpha-1 Antitrypsin Deficiency. (1st September 2014) - Manca, Sandra; Rodriguez, Esther; Huerta, Arturo; Torres, Maria; Lazaro, Lourdes; Curi, Sergio; Pirina, Pietro; Miravitlles, Marc
Abstract: Alpha-1-antitrypsin deficiency (AATD) is an inherited disorder responsible for early onset emphysema associated with a significant impairment of health-related quality of life (HRQoL). Our aim was to assess the usefulness of different instruments to evaluate the HRQoL in patients with AATD compared to non-AATD COPD. Observational, cross-sectional study in which all patients filled out a series of questionnaires: the COPD severity score (COPDSS), the EuroQoL 5-Dimensions (EQ-5D), the Living with COPD (LCOPD) and the COPD Assessment Test (CAT). A total of 96 patients were included, 35 with AATD (mean age 56.5 yrs, 57.1% male and mean FEV1 (%) 48.7% and 61 non-AATD COPD (70.3 yrs, 80.3% men and FEV1 (%) 47%. The questionnaire scores were similar, with a tendency towards worse scores in AATD for the EQ-5D (VAS) (64.8 (20.2) vs. 71.6 (17.1); p = 0.08). The correlations between the different scores and FEV1(%) were significant in both groups for COPDSS and LCOPD, but not for CAT and EQ-5D. In general, the correlations of scores with FEV1 (%) were stronger for AATD compared with non-AATD COPD patients: COPDSS r = −0.570, p < 0.01 for AATD and r = −0.260, p < 0.05 for COPD; LCOPD r = −0.502, p < 0.001 for AATD and r = −0.304, p < 0.05 for non-AATD COPD. Patients with AATD have a similar degree of HRQoL impairment as older subjects with non-AATD COPD and showed a stronger correlation between HRQoL measurements and lung function impairment compared with non-AATD COPD. This may be related to the characteristics of the disease in these patients who are usually younger, with less co-morbidity and lower smoking consumption.